High Prevalence of MYO6 Variants in an Austrian Patient Cohort With Autosomal Dominant Hereditary Hearing Loss. Issue 6 (July 2021) - Frohne, Alexandra; Koenighofer, Martin; Liu, David Tianxiang; Laccone, Franco; Neesen, Juergen; Gstoettner, Wolfgang; Schoefer, Christian; Lucas, Trevor; Frei, Klemens; Parzefall, Thomas
Abstract : Introduction: Genetic hearing loss (HL) is often monogenic. Whereas more than half of autosomal recessive (AR) cases in Austria are caused by mutations in a single gene, no disproportionately frequent contributing genetic factor has been identified in cases of autosomal dominant (AD) HL. The genetic characterization of HL continues to improve diagnosis, genetic counseling, and lays a foundation for the development of personalized medicine approaches. Methods: Diagnostic HL panel screening was performed in an Austrian multiplex family with AD HL, and segregation was tested with polymerase chain reaction and Sanger sequencing. In an independent approach, 18 unrelated patients with AD HL were screened for causative variants in all known HL genes to date and segregation was tested if additional family members were available. The pathogenicity of novel variants was assessed based on previous literature and bioinformatic tools such as prediction software and protein modeling. Results: In six of the 19 families under study, candidate pathogenic variants were identified in MYO6, including three novel variants (p.Gln441Pro, p.Ser612Tyr, and p.Gln650ValfsTer7). Some patients carried more than one likely pathogenic variant in known deafness genes. Conclusion: These results suggest a potential high prevalence of MYO6 variants in Austrian cases of AD HL. The presence of multiple rare HL variants in some patients highlights the relevance of considering multiple-hit diagnoses for genetic counseling and targeted therapy design. Abstract : Supplemental Digital Content is available in the text